Continuum of Alliance: A Proposed Model for Understanding the Relationship Between Adult Education and Human Resource Development - Jill Zarestky; Joshua Collins (Adult Education Research Conference, 2016)
The relationship between Adult Education and Human Resource Development has been modeled or described in various ways but continues to evolve. Building on existing conceptions, we present an alternative model for understanding the fields as distinct and yet complementary.
Keywords: adult education; human resource development; critical perspectives